History of the Establishment of Law Number 11 of 1980 Concerning the Crime of Bribery in Indonesian Football Scoring Regulation - Barasa, Abdur Rachman Parlindungan; Setiyono, Joko (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The problem of bribery is one of the problems that has occurred in society for a very long time. In general, bribes are given to influential people or officials to do or not do something related to their position. People who give bribes usually give bribes so that their wishes are achieved, either in the form of certain benefits or to be free from punishment or legal process. This writing, apart from being an assessment of the final project, also aims to explain the history of the development of Law No. 11 of 1980 concerning the Crime of Bribery in eradicating score-fixing in soccer. The data used is secondary data in collecting information from various reading sources. Law Number 11 of 1980 is a tool to eradicate bribery in the sports and private sector that is suitable for eliminating all forms of bribery, because this law is an extension of the Criminal Code, so it is still relevant to be used in eradicating bribes in football.